Pengaruh Rendaman pada Indirect Tensile Strength Campuran AC-BC dengan Limbah Plastik sebagai Agregat Pengganti - Tajudin, Anissa Noor; Suparma, Latif Budi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
The pavement vulnerability of moisture and the risk of environment quality depression caused by plastic waste became the main reason of the effort to increase pavement strength with the use of plastic waste. This study was conducted to understand moisture effect to the fatigue risk with Indirect Tensile Strength (ITS) of AC-BC Hotmix with the use of plastic waste as aggregate substitution. The variance of plastic waste used are 0%, 25%, and 50% of aggregate volume passing sieve No. 4 and retaining on sieve No. 8. The test was conducted with the immersion time of 30 minutes, 1 day, 2 days, 4 days, and 7 days. The result of ITS test showed that longer immersion time will make Tensile Strength Ratio (TSR) become lower. TSR values of 0% plastic waste at the immersion time of 30 minutes, 1 day, 2 days, 4 days, and 7 days respectively are 100%; 79,13%; 62,18%; 54,19%; and 44,25%. For 25% plastic waste are 100%,  82,12%, 66,68%, 64,03%, and 56,91%. And for the 50% plastic waste are 100%, 96,21%, 84,34%, 80,53%, and 76,21%.